PEMBERDAYAAN PEREMPUAN DESA MELALUI PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN KEWIRAUSAHAAN LOKAL - Hanatasya Aulia Risda Puspitasari; Tarrisya Durroh Fitrinda; Giyo Sekhan Abdillah; Izzat Rahman; Dhian Satria Yudha Kartika (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Women's empowerment in Penggaron Village, Mojowarno District, Jombang Regency has an important role in encouraging local economic growth, especially through entrepreneurship development. This article discusses the results of a digital marketing training program aimed at women in Penggaron Village, Mojowarno District, Jombang Regency. This training aims to improve their digital skills, especially in utilizing social media and other online platforms to promote local products. The methods used include face-to-face training sessions, online tutorials, and direct assistance in implementing digital marketing strategies. The results of this training show a significant increase in participants' understanding of digital marketing techniques, as well as an increase in online sales of local products. Furthermore, this training was also successful in strengthening women's community networks in the village, encouraging collaboration in entrepreneurial activities. Thus, this training not only improves individual skills but also has a positive impact on the village economy as a whole.